Types of 23S Ribosomal RNA Point Mutations Affecting Eradication Rates in Clarithromycin-Based Triple Therapy - Gihong Park; Bokyung Kim; Hyunsoo Chung; Sang Gyun Kim; Soo-Jeong Cho (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Objectives The A2142G and A2143G mutations in the 23S ribosomal ribonucleic acid (rRNA) of Helicobacter pylori are the most common mutations associated with clarithromycin resistance. This study aimed to determine the differences in H. pylori eradication rates in patients infected with bacteria carrying the A2142G and A2143G mutations who were treated with clarithromycin-based triple therapy. Methods Data from a previous randomized controlled trial were analyzed retrospectively. Eradication rates were compared based on the presence of H. pylori carrying the A2142G and A2143G mutations. A meta-analysis was also conducted of relevant studies containing data regarding patients who received clarithromycin-based therapy due to infections with H. pylori harboring 23S rRNA mutations. Results No significant difference was observed in H. pylori eradication rates between patients infected with wild-type bacteria (95.7% [44/46]) compared with those infected with bacteria carrying the A2142G mutation (100.0% [3/3]; p>0.9). However, the eradication rate was significantly lower for patients infected with bacteria carrying the A2143G mutation (16.7% [1/6]; p<0.001) than for those infected with wild-type bacteria or bacteria with the A2142G mutation (100.0% [3/3]; p=0.048). In the meta-analysis, the between-group comparisons yielded similar results. Although patients infected with bacteria having the A2142G mutation exhibited no significant risk difference (RD) for eradication compared with those infected with wild-type bacteria (RD=-0.05 [-0.18 to 0.08]; I2=0%; p=0.42), those infected with bacteria having the A2143G mutation demonstrated a lower H. pylori eradication rate compared with patients infected with either wild-type (RD=0.72 [0.64–0.80]; I2=0%; p<0.001) or A2143G mutant bacteria (RD=0.76 [0.61–0.91]; I2=0%; p< 0.001). Conclusions: The A2143G mutation may play a more significant role in clarithromycin triple therapy H. pylori eradication failure than does the A2142G mutation. Additionally, H. pylori strains with the A2142G mutation can be treated effectively with clarithromycin-based triple therapy.